If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -8 = p + -5 Reorder the terms: -8 = -5 + p Solving -8 = -5 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -8 + -1p = -5 + p + -1p Combine like terms: p + -1p = 0 -8 + -1p = -5 + 0 -8 + -1p = -5 Add '8' to each side of the equation. -8 + 8 + -1p = -5 + 8 Combine like terms: -8 + 8 = 0 0 + -1p = -5 + 8 -1p = -5 + 8 Combine like terms: -5 + 8 = 3 -1p = 3 Divide each side by '-1'. p = -3 Simplifying p = -3
| -10b+2b+b=0 | | 5x+17x-8=180 | | 2(1.2)= | | (-76)+(-84)= | | (3x-6)(3x-6)=0 | | 27-9x=4x+8 | | 4(x+9)+5x= | | 2x-5=?(x+4) | | (-15)+(-7)= | | 21x^4=2+x^2 | | 2-8x/1 | | 4(x+5)=3(x-6)+x | | -2(7-y)+4=44 | | 5/16*40n | | 6b^2-40=-8b+2b^2 | | .2-y=-.05x | | (x+9)(x-5)/(5x+4) | | -17+x/8=15 | | -2.6d-3.4d= | | 3(4x-6)=3(4x-3) | | 5/4=-5/3+s | | 23/4x=67/8 | | -4(5t-3)+8t=7t-2 | | (4x-6)=3(4x-3) | | x+6/5+x+3/x=3 | | 7y+5=-6y-21 | | 2z+2=2-2z | | 6x+20=4x-36 | | 4r+7=-43 | | n^2+n=2n | | 7h-10=-4 | | -1-7x-6(-7-x)=36 |